Effect of Polluted Water on Seeds of Phaseolus radiatus L. - Madhusree Naidu, K.; Raman, G.K. (Asian Journal of Chemistry, 2010)
Seeds of Phaseolus radiatus L. were treated with different concentrations of distillery effluent. Catalase (Ec 1.11.1.6) activity and chlorophyll contents were studied. In 25%, 50% and 100% of effluent the catalase activity and chlorophyll contents were decreased.